SSM Annual Scientific Meeting 2021
DOI: 10.1136/jech-2021-ssmabstracts.34
|View full text |Cite
|
Sign up to set email alerts
|

OP34 Ethnic and educational inequalities in COVID-19 vaccine hesitancy: cross-sectional analysis of the UK household longitudinal study

Abstract: were daily, weekly, monthly, every 3 months or never. Multivariate logistic regression on weighted data was performed to assess variation by sex, age group (50 to state pension age (SPA), SPA to 74, 75 and over), and wealth quintile. Results 5,142 core participants responded to both W9 and CW1. Of these, 553 (10.75%; 95% confidence interval (CI) 9.71 to 11.89) reported never using the internet in W9 and 733 (14.26%; 13.05 to 15.57) in CW1. Of those aged 75 and older, 320 (30.64%; 26.87 to 34.87) were 'never us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
3
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 0 publications
2
3
1
Order By: Relevance
“…A higher vaccine hesitancy was identified among ethnic minority groups and SE disadvantaged groups (i.e. with lower levels of education and income, unemployment, and poor knowledge of COVID-19) [27][28][29]. This is again in line with our results showing a lower COVID-19 vaccine uptake among non-European migrants and SE disadvantaged groups.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…A higher vaccine hesitancy was identified among ethnic minority groups and SE disadvantaged groups (i.e. with lower levels of education and income, unemployment, and poor knowledge of COVID-19) [27][28][29]. This is again in line with our results showing a lower COVID-19 vaccine uptake among non-European migrants and SE disadvantaged groups.…”
Section: Discussionsupporting
confidence: 91%
“…Prior to the implementation of COVID-19 vaccination, numerous studies have investigated the SD and SE determinants associated with vaccine hesitancy that may lead to a lower intention to get the vaccine. Some have shown that being a female and having children were associated with a lower acceptance of the COVID-19 vaccine [27][28][29][30]. This sex difference was not observed in our results which show a lower COVID-19 vaccine uptake among men, compared to women.…”
Section: Discussioncontrasting
confidence: 74%
See 3 more Smart Citations